Application of Rhizobium Inoculum and Plant Population on Nodulation and Productivity of Edamame (Glycine max (L.) Merr.) - Rochman, Fajar; Rahmadi, Rizky; Sari, Evi Yunita (Politeknik Negeri Bengkalis, 2024)
Root nodulation is a crucial process for legumes, including edamame (Glycine max (L.) Merr.), as it enablesbiological nitrogen fixation, enhancing nitrogen availability for plant growth. The implementation of Rhizobium inoculumhas been demonstrated to reduce the necessity for synthetic fertilizers, thereby enhancing the health and yield of the plantsin question. Furthermore, optimal plant population management ensures adequate access to light, water, and nutrients,maximizing productivity. The combination of Rhizobium inoculation and population management represents a crucialstrategy for enhancing the productivity and sustainability of legume crops, such as edamame. This study examines theimpact of Rhizobium inoculation and plant population management on the nodulation and productivity of edamame. Theresearch was conducted using a randomized block design, with two factors: the application of Rhizobium (Bradyrhizobiumjaponicum) at two levels (without inoculation and with inoculation) and plant spacing (20 x 15 cm and 20 x 30 cm). Eachtreatment was replicated five times. The observed parameters included number of root nodulations, plant height, leaf area,leaf greenness, number of filled and empty pods, weight of filled and empty pods, wet weight, and 100 seed weight. Thedata were subjected to analysis of variance, followed by Duncan's Multiple Range Test. The findings indicated thatRhizobium inoculation markedly enhanced root nodulation, with the 20 x 15 cm spacing in conjunction with inoculationyielding the highest total nodulation, number and wight filled pods, wet weight, and 100 seed weight.